Buddy Emmons : Steel Guitar Icon - Fishell, Steve (Book collections on Project MUSE., 2022)
"The acknowledged maestro of the pedal steel guitar, Buddy Emmons lent his unparalleled virtuosity to over five decades of hit recordings and set standards that remain the benchmark for musicians today. Steve Fishell's merger of biography and memoir draws extensively on in-depth interviews with Emmons and the artist's autobiographical writings. Emmons went from playing strip clubs to a Grand Ole Opry debut with Little Jimmy Dickens at age 18. His restless experimentation led to work with Ernest Tubb and Ray Price--and established him in a career that saw him play alongside a who's who of American music. Fishell weaves in stories and anecdotes from Willie Nelson, Brenda Lee, Linda Ronstadt, Pat Martino, and many others to provide a fascinating musical and personal portrait of an innovator whose peerless playing and countless recordings recognized no boundaries. A one-of-a-kind life story, Buddy Emmons expands our view of a groundbreaking artist and his impact on country music, jazz, and beyond"--